P451 Efficacy and safety of tofacitinib in the treatment of patients with active, moderate to severe, Ulcerative Colitis: a systematic review and meta-analysis. (27th May 2021) - Khorshid Fasge, M; Dorgham, D; Sharobim, A; Attia, M; Hussein, M; Dorgham, N
Abstract: Background: To perform a systematic review and meta-analysis to discuss the efficacy and safety of tofacitinib in patients with moderate to severe ulcerative colitis (UC). Methods: We searched PubMed, Scopus, Web of Science, in addition to Cochrane Central, until May 2020 using relevant keywords. We included randomized controlled trials (RCTs) in addition to cohort studies that compared tofacitinib oral treatment versus placebo in patients with active UC, with a moderate to severe degree. Quality of included RCTs was assessed by the Cochrane risk of bias assessment tool, whereas the Newcastle-Ottawa scale was applied to assess for bias sources in included cohort studies. Data were pooled, after being extracted, from eligible articles in the review manager software, or the open meta-analyst software. Dichotomous outcomes were pooled as risk ratios (RR) under the fixed effect model, while continuous outcomes were pooled as standardized mean difference (SMD) under the random-effects model. Results: pooling data from seven RCTs and four cohort studies, 2728 patients, showed that tofacitinib therapy was superior to placebo in inducing a clinical response in UC patients after eight weeks (p = 0.0001) and 26 weeks, in a proportion 0.4 of patients who took tofacitinib 10 mg BID. Additionally, tofacitinib treatment was associated with significantly higher events of clinical remission of UC, after eight weeks (RR= 3.12, 95% CI [2.34, 4.16], p < 0.0001). Likewise, endoscopic, deep, in addition to symptomatic remission rates were higher in the tofacitinib group, compared to the group of placebo (p ≤ 0.008). Most of the drug-related adverse events were comparable between tofacitinib and placebo groups. However, tofacitinib treatment was associated with fewer serious adverse events (RR= 0.68, 95% CI [0.48, 0.98], p = 0.04); adverse events that led to drug discontinuation (RR= 0.53, 95% CI [0.39, 0.73], p< 0.0001); and worsening of UC (RR= 0.48, 95% CI [0.38, 0.61], p < 0.00001). On the other hand, the placebo group had fewer overall infections (p = 0.002); and elevation in laboratory parameters, including LDL cholesterol, total cholesterol, and triglycerides. Conclusion: Our systematic review and meta-analysis showed that, in patients with active moderate to severe UC, tofacitinib treatment was superior to placebo in inducing clinical response and remission, with less adverse reactions. Additionally, treatment with tofacitinib showed beneficial quality of life and survival benefits for UC patients. Future clinical trials should study the effect of higher doses of tofacitinib in larger RCTs, with longer follow up periods.